Curcumin nanoformulations for antimicrobial and wound healing purposes. (15th February 2021) - Salehi, Bahare; Rodrigues, Célia F.; Peron, Gregorio; Dall'Acqua, Stefano; Sharifi‐Rad, Javad; Azmi, Lubna; Shukla, Ila; Singh Baghel, Uttam; Prakash Mishra, Abhay; Elissawy, Ahmed M.; Singab, Abdel Nasser; Pezzani, Raffaele; et al.
Abstract : The development and spread of resistance to antimicrobial drugs is hampering the management of microbial infectious and wound healing processes. Curcumin is the most active and effective constituent of Curcuma longa L., also known as turmeric, and has a very long and strong history of medicinal value for human health and skincare. Curcumin has been proposed as strong antimicrobial potentialities and many attempts have been made to determine its ability to conjointly control bacterial growth and promote wound healing. However, low aqueous solubility, poor tissue absorption and short plasma half‐life due its rapid metabolism needs to be solved for made curcumin formulations as suitable treatment for wound healing. New curcumin nanoformulations have been designed to solve the low bioavailability problem of curcumin. Thus, in the present review, the therapeutic applications of curcumin nanoformulations for antimicrobial and wound healing purposes is described.